Biophotonics of native silk fibrils - Shimanovich, U; Pinotsi, D; Shimanovich, K; Yu, N; Bolisetty, S; Adamcik, J; Mezzenga, R; Charmet, J; Vollrath, F; Gazit, E; Dobson, C; Schierle, G; et al. (Wiley, 2018)
Native silk fibroin (NSF) is a unique biomaterial with extraordinary mechanical and biochemical properties. These key characteristics are directly associated with the physical transformation of unstructured, soluble NSF into highly organized nano- and microscale fibrils rich in β-sheet content. Here, it is shown that this NSF fibrillation process is accompanied by the development of intrinsic fluorescence in the visible range, upon near-UV excitation, a phenomenon that has not been investigated in detail to date. Here, the optical and fluorescence characteristics of NSF fibrils are probed and a route for potential applications in the field of self-assembled optically active biomaterials and systems is explored. In particular, it is demonstrated that NSF can be structured into autofluorescent microcapsules with a controllable level of β-sheet content and fluorescence properties. Furthermore, a facile and efficient fabrication route that permits arbitrary patterns of NSF microcapsules to be deposited on substrates under ambient conditions is shown. The resulting fluorescent NSF patterns display a high level of photostability. These results demonstrate the potential of using native silk as a new class of biocompatible photonic material.